Analysis of the influence of selected elements on the functioning of the bone tissue - Łabądź, Dawid Dominik; Skolarczyk, Justyna Magdalena; Pekar, Joanna; Nieradko-Iwanicka, Barbara (Journal of Education, Health and Sport, 2017)
The Bone as part of organ motion is a rich source of research related to Physiology and pathology. Orthopaedics as a bone test for pathology, primarily associated with the disorder the correct structural axis, and impaired motor function. However, bones are also a rapidly acting, living element significantly influencing the metabolism of the whole body. Impact on we cannot detect virtually all elements of the environment, starting with nutrition, the composition of the air. Often the subject of research are complex chemical compounds, forgetting that their basic building blocks-atoms of chemical elements - can have a significant impact on the functioning of the body. Studies show that calcium supplementation in reducing the risk of fracture osteoporetycznych. Especially with the level of calcium interferuje phosphorus, which intake should be strictly controlled because of the risk of acidification of the body. Some elements such as zinc, selenium, can interfere with the absorption of harmful compounds, and their supplementation seems to be particularly beneficial and interesting. Element of the application calls the big emotions is also fluoride - which compounds even though applications in dentistry, may cause toxic effects on bone. Element whose derivatives due to the environmental pollution commonly surrounds us is so that cadmium, which calls the strongly negative impact not only on bone tissue, but also a variety of other tissues and organs. This work is an attempt at synthetic summary of available knowledge about the elements that build bone, and its metabolism affecting positively or negatively.